2003
DOI: 10.1086/374368
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Plant Functional Variation: Traits, Spectra, and Strategies

Abstract: Variation in plant functional traits results from evolutionary and environmental drivers that operate at a variety of different scales, which makes it a challenge to differentiate among them. In this article we describe patterns of functional trait variation and trait correlations within and among habitats in relation to several environmental and trade-off axes. We then ask whether such patterns reflect natural selection and can be considered plant strategies. In so doing we highlight evidence that demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
1,076
6
43

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,212 publications
(1,176 citation statements)
references
References 150 publications
(268 reference statements)
51
1,076
6
43
Order By: Relevance
“…Confirming the results of numerous previous studies on plant responses to shading (Reich et al, 2003;Rozendaal et al, 2006;Gianoli and Saldana, 2013;Feng and van Kleunen, 2014), our meta-analysis showed that most plants produced leaves with a higher SLA when shaded. This plastic response of SLA results in thinner, and relatively larger, leaves, and consequently should enhance light capture per gram of leaf tissue and thus mass-based photosynthesis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Confirming the results of numerous previous studies on plant responses to shading (Reich et al, 2003;Rozendaal et al, 2006;Gianoli and Saldana, 2013;Feng and van Kleunen, 2014), our meta-analysis showed that most plants produced leaves with a higher SLA when shaded. This plastic response of SLA results in thinner, and relatively larger, leaves, and consequently should enhance light capture per gram of leaf tissue and thus mass-based photosynthesis.…”
Section: Discussionsupporting
confidence: 89%
“…SLA is also a major trait in the worldwide leaf economics spectrum, which reflects the range of fast to slow returns on nutrient and dry mass investment in leaves among species (Wright et al, 2004;Flores et al, 2014). Plants usually develop a higher SLA when grown under low-light conditions (Reich et al, 2003;Rozendaal et al, 2006;Feng and van Kleunen, 2014). This response could help plants to increase the efficiency of light capture and maximize carbon gain in such environments (Evans and Poorter, 2001;Gommers et al, 2013), because SLA tends to scale positively with the mass-based light-saturated photosynthetic rate (Pérez-Harguindeguy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…5) might have coincided with differences in leaf flushing phenology. In such case, differences in HI patterns might be related to distinct functional traits (Geber and Griffen 2003;Reich et al 2003), represented in the studied clones. Nevertheless, the differences of HI variation patterns between the groups of clones (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…Further, even if we could integrate these original sources, we would not be able to place much confidence in the resulting list of taxa because: (i) there is no standardized global list to assess the validity of the names or circumscriptions of plant taxa 1 ; (ii) there is no global standard for naming variants contained within taxa 2 ; (iii) there are numerous technical and data quality issues with merging and serving data from disparate sources; and (iv) there is no standardized process by which data on distribution and abundance of plant taxa can be combined with information from plant physiology, genomics, and phylogeny. The last point is especially important because understanding why species are limited in where they grow requires genetic and physiological knowledge of traits that affect how an individual responds to the environment [29]. We can describe observed vegetation shifts across continents as temperatures rise, for example, but will not be able to predict future shifts until we know how individuals and taxa change across environmental gradients and how they react to changes in temperature and precipitation.…”
Section: Ib -The Barriers -mentioning
confidence: 99%